Geological evolution of the Sinus Iridum basin. (December 2020) - Hu, Teng; Kang, Zhizhong; Massironi, Matteo; Hiesinger, Harald; van der Bogert, Carolyn H.; Gamba, Paolo; Brunetti, Maria Teresa; Melis, Maria Teresa
Abstract: As a semi-enclosed crater basin on the northwest rim of Imbrium basin, Sinus Iridum is a key site to investigate the geological characteristics at the intersection of two basins. For this reason, we focused on model age determination in Sinus Iridum basin using Chang'E−2 high-resolution images coupled with compositional maps from the Clementine data sets, as well as with digital elevation models (DEMs) from the Lunar Orbiter Laser Altimeter (LOLA) onboard the Lunar Reconnaissance Orbiter (LRO). With these datasets we identified different geologic units onto which we performed model age determinations based on crater counting. This systematic analysis of the Sinus Iridum basin shows that the age of the oldest exposed basaltic unit is 3.37 ​Ga (Imbrian age), while the youngest, a mare basalt unit that enters the basin from Imbrium basin, is 1.24 ​Ga (late Eratosthenian). In general, the ages of the geologic units inside the Sinus Iridum basin gradually decrease from the northeast to the southwest, with the only exception of the young units being located in the north-eastern area. We conclude that the crater size-frequency distributions (CSFD) reflect a multi-layer sequence, suggesting multiple resurfacing events inside Sinus Iridum. The model age determinations identify several infilling events of basalts ranging from 3.37 ​Ga to 1.24 ​Ga, which are all derived mare basalt flows from the Imbrium basin. Highlights: Based on Chang'E-2 and Clementine data, a new geological map is produced for the Sinus Iridum basin. The oldest geologic unit is 3.37 Ga, likely the age of the first common infillings of Sinus Iridum and Imbrium basins. The youngest geologic unit is 1.24 Ga, and this layer's thickness (34.9m) is consistent with Yutu rover's result (35m). The Sinus Iridum basin was deeply affected by the lava flows infilled from neighboring Imbrium basin in different periods.